2017
DOI: 10.1016/j.stemcr.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

SOX7 Is Required for Muscle Satellite Cell Development and Maintenance

Abstract: SummarySatellite cells are skeletal-muscle-specific stem cells that are activated by injury to proliferate, differentiate, and fuse to enable repair. SOX7, a member of the SRY-related HMG-box family of transcription factors is expressed in quiescent satellite cells. To elucidate SOX7 function in skeletal muscle, we knocked down Sox7 expression in embryonic stem cells and primary myoblasts and generated a conditional knockout mouse in which Sox7 is excised in PAX3+ cells. Loss of Sox7 in embryonic stem cells re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It is possible that the different expression patterns of Sox genes in tongue muscles could be correlated with the onset of these stages, although the molecular mechanisms regulating the initiation of each phase during tongue development remain unclear. It has been shown that Sox7, 15, 17 and 18 are involved in the function of satellite cells after birth, although these are not exerted at embryonic stages [ 11 13 ]. Therefore, a punctate expression pattern of Sox7, 17, and 18 observed in the embryonic tongue are likely to represent vascularization of the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the different expression patterns of Sox genes in tongue muscles could be correlated with the onset of these stages, although the molecular mechanisms regulating the initiation of each phase during tongue development remain unclear. It has been shown that Sox7, 15, 17 and 18 are involved in the function of satellite cells after birth, although these are not exerted at embryonic stages [ 11 13 ]. Therefore, a punctate expression pattern of Sox7, 17, and 18 observed in the embryonic tongue are likely to represent vascularization of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Spatiotemporal expression patterns of Sox genes have been reported in tooth and pancreas development [ 7 , 8 ]. In the trunk and limb region, it has been reported that Sox6 is involved in skeletal muscle formation, while Sox7, 15, 17, and 18 have been shown to be related to function of satellite cells [ 9 13 ]. Although Sox2 has been reported to be involved in the development of tongue papillae [ 14 ], the expression pattern of other Sox genes during the entire development of the tongue remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a Sox7 fl mutant mouse has been reported, revealing the genetic interaction of SOX7 with SOX17 in developmental angiogenesis ( Kim et al, 2016 ). Furthermore, during revisions for this study, a muscle-specific ablation of Sox7 ( Pax3 Cre/+ ;Sox7 fl/fl ) was reported, showing upregulation of Sox17 and Sox18 in the absence of Sox7 ( Rajgara et al, 2017 ). Nevertheless, Sox7 -deficient muscles demonstrated severe phenotypes in homeostatic and regeneration conditions ( Rajgara et al, 2017 ), similar to Sox17 ablation in myogenic cells ( Figures 3 – 6 ).…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, during revisions for this study, a muscle-specific ablation of Sox7 ( Pax3 Cre/+ ;Sox7 fl/fl ) was reported, showing upregulation of Sox17 and Sox18 in the absence of Sox7 ( Rajgara et al, 2017 ). Nevertheless, Sox7 -deficient muscles demonstrated severe phenotypes in homeostatic and regeneration conditions ( Rajgara et al, 2017 ), similar to Sox17 ablation in myogenic cells ( Figures 3 – 6 ). Future studies analyzing the impact of ablating both SOX7 and SOX17 for muscle stem cell function will be of interest.…”
Section: Discussionmentioning
confidence: 82%
“… 75 SOX7 has been recognized as a member of the SOX (SRY-related HMG-box) family of transcription factors, mainly involving in tumorigenesis and development, 76 , 77 as well as muscle satellite cell development. 78 The PMS2P11 gene is a pseudogene with unknown functions. Further investigation is necessary to determine the influence of these genes’ expression in brain tissues on the occurrence and development of OSA and BMI.…”
Section: Discussionmentioning
confidence: 99%